Modeling Economy of Information Security of Business Entity Based on Simplex-Method - V. A. Sizov (Plekhanov Russian University of Economics, 2021)
In the field of information security it is always necessary to support a required level of protection, which can cause serious financial costs. The more information you should protect, the more money you should spend on it. The expert on information security shall both develop methods aimed at improvement of information system condition and save funds. To resolve these tasks different mathematic models can be used, such as methods of linear programming. Linear programming is a mathematic subject dealing with theory and methods of resolving extreme tasks on sets of n-dimensional space given by systems of linear equations and inequalities. These mathematic models should be used after assessing a possible damage after information leakage. In the article the authors study the task of company cost optimization. In the majority of cases total costs can be written as a linear equation. At the same time there are some restrictions on a certain root of equation. Simplex-method provides an opportunity to find the solution without using considerable technical capacities of computing.